Financial crises and recession in the global economy - Allen, Roy E. , 1957- (Edward Elgar, 2009)
Explaining the rise and fall of economies in Asia, Central America and Europe, this book explains major financial instabilities and trends across the global economy since the 1970s, including the crisis that began in 2008 and the long boom that preceded it